Penerapan Model Pembelajaran Problem-Based Learning terhadap Kemampuan Berpikir Kritis dan Aktivitas Belajar Peserta Didik pada Materi Hidrolisis Garam - Zahro, Mawadatuz; Lutfianasari, Ulfa (Universitas Negeri Semarang, 2024)
This research is motivated by the existence of learning problems at MAN 1 Semarang City which still uses conventional learning models, so that students find it difficult to understand the subject matter delivered by the teacher. Therefore the researchers applied the Problem Based Learning (PBL) learning model with the hope that learning would be more interesting and able to understand students so that the expected results could be achieved. This study aims to find out how students' critical thinking skills and learning activities are carried out through the application of the Problem Based Learning (PBL) learning model in Salt Hydrolysis material. This research is a quantitative research with a quasi-experimental design with nonequivalent control group design method. Methods of data collection using test questions (critical thinking skills) and observation (learning activities). The application of PBL in the learning process can have a positive influence on students' critical thinking skills and activities. This is proven through the t-test analysis of critical thinking skills tcount = 8.071 and ttable =. 2,021. As for learning activities tcount = 5.441 ttable = 2.021, it is concluded that learning using the PBL model is more effective than learning applied using conventional models.